Phenotypic Clumping Decreases With Flock Richness in Mixed-Species Bird Flocks - Bangal, Priti; Sridhar, Hari; Shanker, Kartik (Frontiers in Ecology and Evolution, 2021)
Animals that live in groups may experience positive interactions such as cooperative behavior or negative interactions such as competition from group members depending on group size and similarity between individuals. The effect of group size and phenotypic and ecological similarity on group assembly has not been well-studied. Mixed-species flocks are important subsets of bird communities worldwide. We examined associations within these in relation to flock size, to understand rules of flock assembly, in the Western Ghats of India. We examined the relationship between phenotypic clumping and flock richness using four variables – body size, foraging behavior, foraging height and taxonomic relatedness. Using a null model approach, we found that small flocks were more phenotypically clumped for body size than expected by chance; however, phenotypic clumping decreased as flocks increased in size and approached expected phenotypic variation in large flocks. This pattern was not as clear for foraging height and foraging behavior. We then examined a dataset of 55 flock matrices from 24 sites across the world. We found that sites with smaller flocks have higher values of phenotypic clumping for body size and sites with larger flocks are less phenotypically clumped. This relationship was weakly negative for foraging behavior and not statistically significant for taxonomic relatedness. Unlike most single-species groups, participants in mixed-species flocks appear to be able to separate on different axes of trait similarity. They can gain benefits from similarity on one axis while mitigating competition by dissimilarity on others. Consistent with our results, we speculate that flock assembly was deterministic up to a certain point with participants being similar in body size, but larger flocks tended to approach random phenotypic assemblages of species.